ANALISIS KONTRIBUSI PENGAMALAN AL-QUR’AN TERHADAP KESEHATAN MENTAL (LP2M JAMIAT KHEIR, 2023)
The Al-Qur'an gives instructions to humans to practice it comprehensively, because by practicing the Al-Qur'an it can give confidence that life becomes more meaningful. Someone who sticks to the Qur'an, when he experiences disappointment, he will not feel hopeless and will face it calmly and steadfastly. It is beliefs like these that will keep a person mentally healthy because he avoids feeling anxious, depressed and stressed when he has a problem. In the context of the Qur'an, people who are closer to Allah SWT by increasing their worship (remembrance of Allah SWT), the more peaceful their souls will be and the more able to face disappointments and difficulties in life. The type of research conducted is library research, which is a study that aims to collect data and information with the help of various materials contained in the library, for example in the form of books, notes, papers, and others. other. This means that the problem and data collection come from literature review. The results of the research from the contribution of the practice of the Qur'an to mental health are: (1) calm and peace of mind, (2) developing and utilizing potential, (3) living a meaningful and happy life. Keywords: Practice, Al-Qur'an, Mental health